Standardized equipment reliability and integrity process to achieve world class performance - ST, Susantana (2014)
This paper (part 2) provide a systematic, staged approach to deploy and execute standardized Equipment Reliability and Integrity Process, Sub-processes and Procedures that enable operation and maintenance of facilities to sustain reliability, integrity and Incident Free Operation (IFO) at Oil and Gas Company.The Equipment Reliability and Integrity Process (ERIP) procedures are executed in five stages, minimum performance levels must be achieved in one stage prior to moving to the next stage.Procedures are executed in a prescribed order referred to as stages.ERIP is a Base Business initiative designed to arrest the natural rate of production decline.This is brought about through identifying the opportunities and solutions for optimizing reserves management, improving the reliability of facilities, and optimizing the capacity of existing facilities.Performance is first verified by the Business Unit through self assessment then through formal Global Upstream validation. It has been determined through bench-marking studies of competitors, that company can deliver superior returns by effectively managing its asset base and standardizing processes across its operations. Standardization of common processes holds great promise and can help company achieve its objectives.This ERIP is applicable for the company that has more than one subsidiary.